LAWS OF HISTORY IN THE CONTEXT OF HEGEL'S PHILOSOPHY. THEORETICAL AND METHODOLOGICAL ANALYSIS - Stezhko, Zoya; Kharchenko, Yulia; Shalimova, Natalia (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2022)
Introduction. Georg Hegel's philosophical conception is universal, systematically structured, permeated with uniform principles and logic, and the analysis of reality through the prism of the categorical apparatus of his philosophy acquires the feature of perfection. We focus on understanding the system of categories and principles of Hegel's philosophy as a methodological apparatus that deeply reveals the logic of reality, and reveal the effectiveness of its methodological impact on practice on the example of history. The aim is an analysis of the problems and possibilities of history in the explanation and prediction of social processes in the context of the philosophical concept of Georg Hegel. The tasks to single out and introduce the author's approaches to solving the problems of optimization of socio-historical processes into the stream of philosophical discussion. Research methods correlate with methodological requirements of classical philosophy followed the principles of rationality, objectivity, determinism; categories of necessity, chance, freedom, individual and general, law; philosophical principles of unity of historical and logical, the ascent from the abstract to the concrete; general scientific methods of analysis and synthesis, induction, and deduction. Research results. In the context of Hegel's methodological requirements, the movement of abstraction in the process of cognition is traced; the reasons of impossibility of full rationalization of social and historical processes are analyzed; reasons for the limited methodological possibilities of history are highlighted; a new vision of the place of history as a science in the system of sciences is proposed; new approaches to understanding the categories of law and regularity are proposed; the differences between the categories of necessity and historical necessity are analyzed; the underestimation of the possibilities of argumentation through terminological analysis of the tokens law and freedom is pointed out, which significantly reduces the efficiency of their research and implementation; the underestimation of the ambiguity and multilevel content of the token freedom are pointed out, which can cause a "fan" of possible negative consequences for the state; the danger of the formation of a "dictatorship of arbitrariness" through the absolutization of the content of the category of freedom is substantiated; examples of methodological requirements of philosophy to social and political sciences and practice of their implementation and consequences of ignoring these requirements are given; the need to change priorities in relation to history and philosophical methodology by different groups of the population – with special emphasis on the stratum of politicians in modern liberal democracies is substantiated; the place and role of irrational and subjective factors in the "canvas" of knowledge of the laws of social development is specified; the methodological possibilities of Hegel's philosophy in optimization of social and historical processes are illustrated on the example of implementation of the category of measure; the objective and subjective factors that cause difficulties in this process are identified and analyzed. Discussion. In the academic publications of Ukraine, there is a lack of clarity and fragmentation in the definition of both the general state of the higher education system and the prospects for its renewal. Соnclusion. As a result of a comprehensive analysis of the problem stated in the article, it can be argued that the movement of abstraction and rationalization of primary facts, the formation of its own categorical apparatus, etc. place history in close quarters with other basic sciences. And the sarcastic statements of opponents of history as a science, which can be considered an absolutization of one of the positions are more a reflection of its specifics - multilevelness, multifacetedness, ambiguousness, incredible dynamics and subjectivism, which makes history one of the most difficult sciences. The history of the future can also be considered only a manifestation of its specificity: it is both true and false. The options, dates and circumstances, in fact, cannot be predicted. But the main features of events can be explained, modeled, and predicted - within acceptable limits of ambiguity. The specifics of the laws of history include the need for a longer (compared to the natural sciences) support by philosophy. The subjective-irrational moment ("mysticism", according to G. Hegel) in the laws of history is also legitimate: the ratio is able to "inscribe" it in the general background of statistical-probabilistic regularities - it is important not to cross the line of the measure. Based on these methodological requirements, politicians must anticipate possible negative consequences for the state - otherwise it is their fault and their responsibility.